ANALYSIS OF SUPPLY CHAIN PERFORMANCE AND ADDED VALUE OF TEMPEH IN MATARAM CITY - Wuryantoro, W; Ayu, C; Sjah, T (AGROLAND The Agricultural Sciences Journal (e-Journal), 2024)
Supply chain performance measurement presents a valuable opportunity to enhance and advance supply chain management practices across various industries, including the tempeh agroindustry. The research was aimed at analyzing the structure and performance of the supply chain, as well as the added value of the tempeh agroindustry in Mataram city. The study utilized a descriptive method that involved interviewing several respondents. Collected data was analyzed using the Supply Chain Operation Reference (SCOR) method version 9, and Hayami Model Added Value Analysis. The results indicated that the stakeholders involved in the agroindustry supply chain in Mataram city were soybean importers in Java, local soybean supply agents, tempeh agroindustry entrepreneurs, and tempeh retailers. The study found that the tempeh agroindustry supply chain performance attained superior performance in the Reliability, Flexibility, Responsiveness, and Asset attributes. On the other hand, the Total Supply Chain Cost attribute recorded poor performance. Processing one kilogram of soybeans into tempeh yielded an added value of IDR. 9,280.82, with an added value ratio of 43.56%, and is categorized as moderate.